Neurophysiological markers of prospective memory and working memory in typical ageing and mild cognitive impairment. (January 2022) - Crook-Rumsey, Mark; Howard, Christina J.; Hadjiefthyvoulou, Florentia; Sumich, Alexander
Highlights: Poorer conceptual prospective memory (PM) and working memory (WM) performance in mild cognitively impaired older adults (MCI). MCI had deficits in P2 and parietal positivity amplitudes and reorientation negativity (RON) latency. Older adults and MCI had delayed parietal positivity, reduced RON, raised N300 and frontal positivity amplitudes. Abstract: Objective: Prospective memory (PM) —the memory of delayed intentions— is impacted by age-related cognitive decline. The current event-related potential study investigates neural mechanisms underpinning typical and atypical (Mild Cognitive Impairment, MCI) age-related decline in PM. Methods: Young adults (YA, n = 30, age = 24.7, female n = 13), healthy older adults (OA, n = 39, age = 72.87, female n = 24) and older adults with MCI (n = 27, age = 77.54, female n = 12) performed two event-based PM tasks (perceptual, conceptual) superimposed on an ongoing working memory task. Electroencephalographic data was recorded from 128 electrodes. Groups were compared for P2 (higher order perceptual processing), N300/frontal positivity (cue detection), the parietal positivity (retrieval), reorienting negativity (RON; attention shifting). Results: Participants with MCI had poorer performance (ongoing working memory task, conceptual PM), lower P2 amplitudes, and delayed RON (particularly for perceptual PM) than YA and OA. MCI had lower parietal positivity relative to YA only. YA had earlier latencies for the parietal positivity than MCI and OA, and lower amplitudes for N300 (than OA) and frontal positivity (than OA and MCI). Conclusions: Impaired attention and working memory may underpin PM deficits in MCI. Significance: This is the first study to document the role of RON in PM and to investigate neurophysiological mechanisms underpinning PM in MCI.